A mass spectrometric insight into the origins of benign gynecological disorders. Issue 3 (3rd December 2015) - Yang, Huiliang; Lau, Wayne Bond; Lau, Bonnie; Xuan, Yu; Zhou, Shengtao; Zhao, Linjie; Luo, Zhongyue; Lin, Qiao; Ren, Ning; Zhao, Xia; Wei, Yuquan
Abstract : Applications of mass spectrometry (MS) are rapidly expanding and encompass molecular and cellular biology. MS aids in the analysis of in vivo global molecular alterations, identifying potential biomarkers which may improve diagnosis and treatment of various pathologies. MS has added new dimensionality to medical research. Pioneering gynecologists now study molecular mechanisms underlying female reproductive pathology with MS‐based tools. Although benign gynecologic disorders including endometriosis, adenomyosis, leiomyoma, and polycystic ovarian syndrome (PCOS) carry low mortality rates, they cause significant physical, mental, and social detriments. Additionally, some benign disorders are unfortunately associated with malignancies. MS‐based technology can detect malignant changes in formerly benign proteomes and metabolomes with distinct advantages of speed, sensitivity, and specificity. We present the use of MS in proteomics and metabolomics, and summarize the current understanding of the molecular pathways concerning female reproductive anatomy. Highlight discoveries of novel protein and metabolite biomarkers via MS‐based technology, we underscore the clinical application of these techniques in the diagnosis and management of benign gynecological disorders. © 2015 Wiley Periodicals, Inc. Mass Spec Rev 36:450–470, 2017